2007
DOI: 10.1029/2007jf000772
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of steady state fluvial topography above fault‐bend folds

Abstract: [1] In steady state convergent orogens, erosion balances lateral as well as vertical bedrock motions. For simple geometrical reasons, the difference between the total steady state erosion flux and its vertical component is up to 30% for typical fluvial slopes and bedrock streamline inclinations, suggesting that lateral advection is also likely to be expressed topographically. In order to understand these geomorphologic consequences, we focus on steady state topography developed on active fault-bend folds. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 83 publications
(229 reference statements)
6
56
0
Order By: Relevance
“…(1) as in many previous studies (e.g., Willgoose et al, 1991;Kirkby, 1994;Tucker and Slingerland, 1994;Kirby and Whipple, 2001;Miller et al, 2007) as…”
Section: Topographic Evolution Modelmentioning
confidence: 80%
See 2 more Smart Citations
“…(1) as in many previous studies (e.g., Willgoose et al, 1991;Kirkby, 1994;Tucker and Slingerland, 1994;Kirby and Whipple, 2001;Miller et al, 2007) as…”
Section: Topographic Evolution Modelmentioning
confidence: 80%
“…The main features of the topography, however, are considered to be primarily controlled by an advective stream process (Howard, 1994;Kooi and Beaumont, 1996). In fact, the numerical simulation of Miller et al (2007), in which the scale of their target (Siwalik Hills, Nepal) is about 20 km in the horizontal direction, demonstrated that diffusion does not visibly affect the asymmetry of the range under normal conditions. This study identifies the logarithmic relation between the topographic and rock uplift axes for a simple set of conditions (Figs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One example of this is a long-lived fault-bend fold moving over a curving ramp, where the rate of rock uplift in the hangingwall (relative to the footwall) depends on the rate of thrust propagation and on the local dip of the fault plane (e.g. Hurtrez et al, 1999;Miller et al, 2007). Steady, non-uniform landscapes may also be found in transient settings where erosion rates are evolving in both space and time, but temporal variations are relatively subtle over the time scale required to lower the land surface by a depth comparable to the thickness of the soil (e.g.…”
Section: Natural Experiments In Landscape Evolution 1455mentioning
confidence: 99%
“…In south-eastern Australia, Van Der Beek and used a similar model to assess controls on landscape evolution and denudation history. Miller and Slingerland (2006) and Miller et al (2007) used landscape evolution modeling to suggest an explanation for the fact that drainage basins along opposite flanks of mountain ranges are aligned and commonly similar in planform. Miller and Slingerland (2006) and Miller et al (2007) used landscape evolution modeling to suggest an explanation for the fact that drainage basins along opposite flanks of mountain ranges are aligned and commonly similar in planform.…”
Section: Descriptive Studiesmentioning
confidence: 99%